Effectiveness Of Hedging Strategy In Reducing Foreign Currency Risk : A Comparative Study Of Food And Beverage Companies In Singapore, Indonesia, Malaysia - Armedya (Journal of Economic and Business Analysis, 2024)
Abstrac : This study aims to analyze the effectiveness of hedging strategies in reducing foreign exchange risk in food and beverage companies in Singapore, Indonesia, and Malaysia. Using a quantitative approach with a comparative descriptive design, this study involved 30 companies involved in international trade and have implemented hedging strategies. Derivative instruments, such as futures contracts. The results of the regression test show that the hedge ratio (h) value of 0.887 indicates a significant relationship between changes in futures values and changes in spot values, and hedge effectiveness of 87%, which shows the ability of futures contracts to reduce exchange rate volatility. The R Square value of 0.760 indicates that hedging strategies can explain about 76% of the variation in spot value changes. However, factors such as exchange rate fluctuations and monetary policy can affect the effectiveness of hedging in each country, which causes differences in results between Singapore, Indonesia, and Malaysia. This study concludes that although hedging strategies using futures contracts are effective, companies must adjust their strategies to different economic and market conditions in each country to ensure optimal protection against foreign exchange risk. Keywords : Hedging Strategy, Foreign Exchange Risk.